AN ELECTRON ENERGY SPECTRUM AND WAVE FUNCTION IN THE FIELD OF ASYMMETRIC QUANTUM WELL WITH ARBITRARY SHAPE OF THE BOTTOM - Sedrakian, D. M.; Khachatrian, A. Zh. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2002)
A new method for consideration of an electron stationary motion in the field of an arbitrary one-dimensional potential. It is shown that for a case of an electron infinite motion, the problem of determination of wave functions can be represented as Cauchy problem for the one-dimensional Schrodinger equation. For the case of finite motion the equation determining the energy spectrum is found. It is proved, when the spectrum of bound states is know, the problem of building the wave functions of the discrete spectrum can be formulated as Cauchy problem for wave equation as well.